Use of a green (bio) solvent – limonene – as extractant and immiscible diluent for large volume injection in the RPLC‐tandem MS assay of statins and related metabolites in human plasma. (18th April 2012) - Medvedovici, Andrei; Udrescu, Stefan; David, Victor
ABSTRACT: Limonene, considered a green solvent, was successfully used to extract simvastatin, lovastatin, and their hydroxy‐acid metabolites from human plasma samples. The extraction process was followed by the direct injection of a large volume aliquot (100 μL) from the limonene layer into a Zorbax SB‐C18 Rapid Resolution chromatographic column (50 mm length × 4.6 mm i.d. × 1.8 µm d.p.), operated under gradient elution reversed‐phase separation mechanism. Tandem mass spectrometry operated under the multiple reaction monitoring mode was used for detection, providing low quantitation limits in the 0.25–0.5 ng/mL concentration interval. This method was validated and used for quantitation of simvastatin and its hydroxy acid metabolite in incurred plasma samples obtained from two volunteers participating in a bioequivalence study, using lovastatin and its hydroxy analog as internal standards. The results were statistically compared with those produced by means of an alternative RPLC‐tandem MS using protein precipitation with acetonitrile. The quality attributes of the two methods are comparatively discussed. The agreement between the quality characteristics of the two methods and the experimental results obtained on real samples may be considered as a consistent basis for the simultaneous use of limonene as extraction medium and injection diluent for hydrophobic compounds in bioanalytical approaches. Copyright © 2012 John Wiley & Sons, Ltd.